2022
DOI: 10.3776/tpre.2022.v12n2p89-103
|View full text |Cite
|
Sign up to set email alerts
|

Rural secondary STEM teachers’ understanding of the engineering design process

Abstract: Though STEM teacher professional development is known to be beneficial, it is not available equally to educators in all geographic regions. Rural educators face unique challenges not often experienced by their urban and suburban counterparts. This study investigates the impacts of a Research Experiences for Teachers (RET) program on rural math, science, and technology education teachers’ perspectives on how these experiences changed their understanding of the engineering design process (EDP). From 2016 to 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Other researchers have concluded that teacher preparation programs need to consider more comprehensive courses on topics such as communication, technology, curriculum design, the EDP in math and science education, transdisciplinary learning approaches and the implementation of STEM in the classroom (Shahat and Al-Amri, n.d.). Shume et al (2022) suggested that having student teachers conduct their own research regarding STEM can positively impact teacher training programs by helping student teachers develop a more authentic conceptual understanding of engineering design tasks, and it can help them create original problem-solving challenges for students in the classroom. Also, more consideration must be given regarding integrating STEM subjects through reflection on (1) the instruction received during their training; (2) school placement experiences and (3) teaching during microteaching (College of Education at SQU, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have concluded that teacher preparation programs need to consider more comprehensive courses on topics such as communication, technology, curriculum design, the EDP in math and science education, transdisciplinary learning approaches and the implementation of STEM in the classroom (Shahat and Al-Amri, n.d.). Shume et al (2022) suggested that having student teachers conduct their own research regarding STEM can positively impact teacher training programs by helping student teachers develop a more authentic conceptual understanding of engineering design tasks, and it can help them create original problem-solving challenges for students in the classroom. Also, more consideration must be given regarding integrating STEM subjects through reflection on (1) the instruction received during their training; (2) school placement experiences and (3) teaching during microteaching (College of Education at SQU, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Geng, Jong, and Chai (2019) examined teachers' concerns regarding STEM education and found that for teachers to implement STEM education in the classroom successfully they require professional development, pedagogical support and curriculum resources. According to a recent study by Shume, Bowen, Altimus, and Kallmeyer (2022), teacher training that is focused on research and implementing the EDP has an impact on teachers by helping them acquire genuine conceptual knowledge of engineering design tasks and by inspiring them to come up with new problems for their students to solve.…”
Section: The Engineering Design Process In Science Educationmentioning
confidence: 99%
“…Research has established that engineering design process-oriented integrated STEM activities have a positive impact on students' achievement levels in science (Dedetürk, Kirmizigül, and Kaya's, 2021;Ercan & Sahin, 2015;Harwell et al, 2015;Wendell & Rogers, 2013).The significance of incorporating the STEM-EDP into regular classroom practices is underscored by its ability to actively involve students in authentic problem-solving. According to Shume et al (2022), educators express an increased commitment to empowering students with more responsibility throughout the problem-solving process, allowing them additional time to grapple with the iterative nature of design. This aligns with existing research findings, such as those by Bowen et al (2021), which highlight that teachers exhibit higher motivation to integrate the EDP into their instructional methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Alanyazın, ilkokul (Parker vd., 2016), ortaokul (Aydoğan & Çakıroğlu, 2022;English vd., 2017) ve lise seviyesinde (Fan & Yu, 2017) öğrenim görmekte olan öğrenciler ile öğretmen adaylarına (Capobianco & Radloff, 2022;Irmak & Öztürk, 2022;Kuvac & Koc, 2022) uygulanan mühendislik tasarım temelli STEM yaklaşımının etkililiğini göstermektedir. Ayrıca, öğretmenlere verilen eğitimler ile onların mühendislik tasarım temelli STEM yaklaşımı hakkında daha donanımlı olmaları sağlanmıştır (Shume, Bowen, Altimus & Kallmeyer, 2022). Bu araştırmanın odağını, fen bilgisi öğretmen adayları oluşturmaktadır.…”
Section: Introductionunclassified